Multiple sites bullet embolism as a cause of acute abdomen - Bárbara Lôbo de Figueirêdo; Priscylla Jennie Monteiro Rabêlo; Adercio Pereira da Silva; Luiz Eduardo Rafael Moutinho; Olival Cirilo Lucena da Fonseca Neto (Turkish Journal of Emergency Medicine, 2021)
Bullet embolism (BE) is a rare and misdiagnosed phenomenon that can significantly affect the cardiovascular system. It occurs when a bullet enters and migrates through the body vessels in gunshot victims. We report in this article a case of a 25-year-old male patient, victim of penetrating trauma caused by a firearm projectile that presented two embolism destinations with acute ischemic repercussions: the right brachial artery and the branches of the superior mesenteric artery. We quickly performed surgical exploration to assess the level of ischemia and resect the foreign body. To the best of the authors' knowledge, this is the only case of acute vascular abdomen due to BE in the literature. There is no standard treatment for BE, and each case should be studied according to signs and symptoms while considering the risks of the destination vessel for the victim. Imaging is necessary for early diagnosis, and the medical team must be aware of multiple and extraordinary critical ischemia presentations when bullet trajectory suggests embolism.